2016
DOI: 10.1002/2016gl069475
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Region 1 and 2 currents in the quiet and substorm time plasma sheet from THEMIS observations

Abstract: Although Earth's Region 1 and 2 currents are related to activities such as substorm initiation, their magnetospheric origin remains unclear. Utilizing the triangular configuration of THEMIS probes at 8–12 RE downtail, we seek the origin of nightside Region 1 and 2 currents. Our statistical study reveals that both kinds of currents exist in the plasma sheet during quiet and active times. Region 2 currents are deep inside the plasma sheet; Region 1 currents, which are farther away from the neutral sheet, extend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
(77 reference statements)
3
14
0
Order By: Relevance
“…The observed ionospheric flow shear is just what is expected for the footprint of a magnetospheric flow shear that can trigger and maintain a KHI that manifests as omega bands. This flow shear appears near the boundary between R1 and R2 currents, whose magnetospheric location is at or a little (<~5 R E ) tailward of the inner edge of the plasma sheet (e.g., Liu et al, ). With the T96 model we can indeed map the flow shears to this downtail region (Table S1).…”
Section: Summary and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed ionospheric flow shear is just what is expected for the footprint of a magnetospheric flow shear that can trigger and maintain a KHI that manifests as omega bands. This flow shear appears near the boundary between R1 and R2 currents, whose magnetospheric location is at or a little (<~5 R E ) tailward of the inner edge of the plasma sheet (e.g., Liu et al, ). With the T96 model we can indeed map the flow shears to this downtail region (Table S1).…”
Section: Summary and Discussionsupporting
confidence: 90%
“…The plasma sheet flow's ionospheric footprint should be the eastward flow immediately poleward of the flow shear. This eastward flow is within the range of the R1 current which occupies a large portion of the plasma sheet (Liu et al, ) and can become concentrated during active times (Yang et al, , ). When mapped to the equatorial plane, this flow is azimuthally dawnward and in the order of several tens of km/s to 100 km/s.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Classically, the substorm current wedge was considered to be a Region 1‐type current system, with the cross‐tail current diverted into the ionosphere on the dawnside and the return current appearing on the duskside (Mcpherron et al, ). More recently, it has been suggested that the large‐scale structure of the substorm current wedge consists of both Region 1‐ and Region 2‐type current systems, with the Region 2‐type current system forming earthward of the Region 1‐type system (Coxon et al, ; Liu et al, ; Ritter & Luhr, ; Sergeev et al, ). Figure shows that the nightside upward and downward FACs increase in both the premidnight and postmidnight sectors, with the upward current increasing more in the premidnight sector and the downward current increasing more in the postmidnight sector.…”
Section: Resultsmentioning
confidence: 99%
“…This forms a new FAC system (Akasofu & Chapman, ; Mcpherron et al, ) or enhances the magnitude of and moves existing FACs (Friedrich & Rostoker, ; Rostoker, ; Rostoker & Friedrich, ). Recent studies have suggested that the substorm current wedge could also include a R 2 ‐type current system (Coxon et al, ; Liu et al, ; Ritter & Luhr, ; Sergeev et al, ). Some 15–30 min after the substorm onset, the currents begin to reduce toward their presubstorm levels in a period known as the recovery phase.…”
Section: Introductionmentioning
confidence: 99%
“…Their formation ushers in one of the magnetotail's most dramatic and repeatable phenomena, magnetospheric substorms. During the substorm growth phase, both transverse and field‐aligned currents are intensified (see reviews by Baker et al [], Kepko et al [], Ganushkina et al [], and references therein) and well measured by properly configured multispacecraft missions [see, e.g., Artemyev et al , ; Liu et al , , and references therein]. This intensification is accompanied by various transients [e.g., Liu et al , ; Sun et al , ; Birn and Hesse , ; Liu et al , ] or by quasi stationary plasma pressure gradients [e.g., Kepko et al , ; Ganushkina et al , , and references therein].…”
Section: Introductionmentioning
confidence: 99%